2011
DOI: 10.1007/s11270-011-0877-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Behavior of Brilliant Blue FCF by a Fe-Zeolitic Tuff

Abstract: The adsorption of Brilliant Blue FCF from aqueous solution was evaluated using a Fe-zeolitic tuff. The adsorbent was characterized by scanning electron microscopy, IR spectroscopy and X-ray diffraction. Sorption kinetic, isotherms, dose and pH effects were determined and the adsorption behavior was analyzed. Kinetic pseudo-first order and linear isotherm models were successfully applied to the experimental results, indicating that the sorption mechanism is physisorption. Experiments in columns were performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[20] Zeolitic materials are of hydrophilic nature and therefore do not have affinity for organic compounds. Surfactantmodified clinoptilolite has been used for the removal of organic compounds and dyes from aqueous solutions [17] and it has been shown that this zeolitic tuff modified with FeCl 3 is a suitable sorbent for the removal of indigo carmine, [21] remazol yellow, [22] brilliant blue FCF, [23] red 5 and yellow 6 [24] from aqueous solutions. It is important to note that this adsorbent may be regenerated by adding H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Zeolitic materials are of hydrophilic nature and therefore do not have affinity for organic compounds. Surfactantmodified clinoptilolite has been used for the removal of organic compounds and dyes from aqueous solutions [17] and it has been shown that this zeolitic tuff modified with FeCl 3 is a suitable sorbent for the removal of indigo carmine, [21] remazol yellow, [22] brilliant blue FCF, [23] red 5 and yellow 6 [24] from aqueous solutions. It is important to note that this adsorbent may be regenerated by adding H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also important because of the ionization of surface functional groups and the composition of solutions [28]. Figure 5 shows the variation in Cd and Pb sorption capacities at various pH values for the calcium alginate beads and a similar behavior for both metals.…”
Section: Resultsmentioning
confidence: 99%
“…The pH is an important parameter to be considered in sorption processes because it may affect both the properties of the adsorbent and the composition of the solution. It is also important because of the ionization of surface functional groups and the composition of solutions [ 28 ]. Figure 5 shows the variation in Cd and Pb sorption capacities at various pH values for the calcium alginate beads and a similar behavior for both metals.…”
Section: Resultsmentioning
confidence: 99%
“…The U.S. Food and Drug Administration (FDA) has reported that five times increase of consumption in dyes is observed since 1955 to 2009 [1]. Brilliant Blue FCF (BBF) or E113 is a food additive dye which is widely used for ice cream, baked goods, cereals, beverages, blue raspberry flavored products, dessert powders and various dairy products [2,3]. The health effects of BBF on human and animals have broadly been reported including gastrointestinal tumors, neurological disorders, and severe allergies [4].…”
Section: Introductionmentioning
confidence: 99%